A System to Design and Implement the Solar Sensors - Mrs. Sahana D S, Mr. Vinay D M, Dr. Dayanand Lal N, Mr. Kishore C (International Journal of Control and Automation, 2020)
The planet Earth’s nearest star is Sun, like all the stars in Universe Sun can also emits strong radiations across all the spectral regions. The human and human eyes have evolved to the optical region through evolution and can only detect radiation in this small range from 390 nm to 700 nm. Moreover, the latest technology is in the Solar or Sun sensors, specifically for determining cubsat's altitude, which is one of the most significant metrics that actually decides the cubesat's life or death. The Sun emits radiation in all regions of the spectrum that brings us to the essential sensor question that will be taken care in this work. Because of the availability of 'n' number of sensors , which are used to detect radiation such as Infrared rays, Gamma rays, Microwaves etc., any sensor can be selected for the construction of proposed device or else specifically for the payload of cubesat. The current work involves selecting a particular sensor based on its response to all types of environments, as space is not an environment that is not welcoming or would be appropriate or fair to anyone.